2014
DOI: 10.1016/j.applanim.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Zoo visitor effect on mammal behaviour: Does noise matter?

Abstract: a b s t r a c tThe zoo visitor effect is the change in animal behaviour and physiology in response to the presence of a viewing public. It is thought to result from, amongst other things, visitor generated sound (i.e., noise), but this hypothesis has never been explicitly tested. We tested this hypothesis through observations on the behaviour and enclosure use of 12 mammal species held in 12 separate enclosures at the Belo Horizonte Zoo when exposed to different sound pressure levels (i.e., noise) from the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 27 publications
2
79
0
1
Order By: Relevance
“…In the zoo environment anthropogenic noise is common, as sound levels may increase due to visitors, construction, habitat design, and special events. Past studies have evaluated how various sources of noise in the zoo environment influence behavioral and physiological indicators of welfare in a variety of species (e.g., Birke, 2002;Chosy, Wilson, & Santymire, 2014;Davey, 2007;Kight & Swaddle, 2011;Orban, Soltis, Perkins, & Mellen, 2017;Quadros, Goulart, Passos, Vecci, & Young, 2014).…”
mentioning
confidence: 99%
“…In the zoo environment anthropogenic noise is common, as sound levels may increase due to visitors, construction, habitat design, and special events. Past studies have evaluated how various sources of noise in the zoo environment influence behavioral and physiological indicators of welfare in a variety of species (e.g., Birke, 2002;Chosy, Wilson, & Santymire, 2014;Davey, 2007;Kight & Swaddle, 2011;Orban, Soltis, Perkins, & Mellen, 2017;Quadros, Goulart, Passos, Vecci, & Young, 2014).…”
mentioning
confidence: 99%
“…This effect was not found when similar numbers of visitors watched the animals quietly. Larsen et al (2014) (Quadros et al, 2014). Sherwen et al (2014) showed no change in Slender-tailed meerkat Suricata suricatta behaviour when visitor noise was reduced.…”
Section: Introductionmentioning
confidence: 89%
“…() showed that Koalas Phascolarctos cinereus increased their vigilance behaviour in response to visitor noise. A study of 12 mammal species [Brown howler monkey Alouatta guariba , Golden‐headed lion tamarin Leontopithecus chrysomelas , Chimpanzee Pan troglodytes , Gorilla Gorilla gorilla , Yellow breasted capuchin Cebus ( Sapajus ) xanthosternos , Jaguar Panthera onca , Ocelot Leopardus pardalis , Bush dog Speothos venaticus , African elephant Loxodonta africana , Giraffe Giraffa camelopardalis , Waterbuck Kobus ellipsiprymnus , Red deer Cervus elaphus ] in 12 enclosures at Belo Horizonte Zoo in Brazil found mixed results where some animals increased their vigilance in response to greater visitor pressure, although in this case noise was not independent of visitor numbers (Quadros et al ., ). Sherwen et al .…”
Section: Introductionmentioning
confidence: 92%
“…Unlike the female, however, the majority of food patches with the highest GUDs were located either along the visitor area or toward the back of the exhibit. Previous studies suggest that visitor proximity may negatively impact zoo animal behavior and welfare (see Davey, 2007 for a review ;Quadros, Goulart, Passos, Vecci, & Young, 2014;Suárez, Recuerda, & Arias-de-Reyna, 2017); it is therefore possible that the male okapi was more sensitive and possibly threatened by the proximity of human visitors compared to the female. This idea could be tested further by adding additional visual barriers or canopy cover along the exhibit barrier between the visitors and the okapi.…”
Section: Discussionmentioning
confidence: 99%